Reducing economic disparities between rural and urban areas through integrated development – Case study: analysis of the turnover of companies in the AIDA Association, Alba County, Romania - Gavrilă-Paven, Ionela; Olteanu, Emil; Dobra, Iulian Bogdan (Progress in Economic Sciences; No 1 (2014): Progress in Economic Sciences, 2014)
This paper presents a local initiative in Romania, Alba County, which tries to establish general guidelines for the sustainable development of a local community that consists of three towns and eight villages. The analysis conducted in this paper is focused on economic activity. The turnover of the companies located in the eleven localities that compose the Intercommunity Development Association – Alba Iulia have been studied. The authors’ objective is to determine the influences effecting the localities and to establish the core of the economic development of this partnership which is trying to surpass the barriers between rural and urban and to form a community able to valorize its potential according to the principles of sustainable development.